Robotic Resection of Adnexal Masses during Pregnancy - Eichelberger, Kacey Y.; Cantrell, Leigh A.; Balthazar, Ursula; Boggess, Kim A.; Strauss, Robert A.; Boggess, John F. (American Journal of Perinatology, 2013)
Objective To characterize the safety and feasibility of robotic adnexal surgery during pregnancy, and to compare surgical and obstetric outcomes for robotic versus laparoscopic treatment of adnexal masses during pregnancy.Study Design A retrospective cohort study of all cases of robotic resection of adnexal masses in gravid patients performed at our institution between 2006 and 2009 compared with 50 consecutive historic laparoscopic controls performed between 1999 and 2007.Results During the study period, 19 parturients underwent planned robotic resection of adnexal masses, all of which were uncomplicated. Compared with 50 consecutive laparoscopic controls, no differences in operative time, conversion to laparotomy, intraoperative or postoperative complications, or observed obstetric outcomes were apparent. The robotic cohort had a significantly shorter length of hospital stay (p < 0.01) and estimated blood loss (p = 0.02).Conclusion Robotic resection of adnexal masses during pregnancy appears both safe and feasible, with similar surgical outcomes when compared with a historic laparoscopic cohort.
Keywords: adnexal mass; robot; robotic surgery; pregnancy